CYBERBRANDING DALAM MEMBANGUN IDENTITAS MEDIA DARING LOKAL - Tantri Annisa Hanjani (Linimasa : Jurnal Ilmu Komunikasi, 2025)
The presence of online media today is not only seen from the journalistic products owned, adaptation in the development of the industry and media business is currently a new challenge. Online media also needs to build a brand and compete with other online media supported by the excellence and uniqueness itself. The purpose of the research is to examine the reasons Ayobandung.com highlight the locality side as the identity that wants to be raised in cyberbranding activities. The method used by the author is a qualitative method with a case study approach. Data was obtained by observation, depth interview and documentation study.The results of the research show that Ayobandung.com believes that the attractiveness of each locality element can capture business potential, through the locality elements raised, Ayobandung.com wants to compete in the media industry as well as want to build media literacy for the community that raises the local side around Greater Bandung.